Assessing the Relative Growth in Motorcycle Ownership as compared to the Growth in Private car Ownership: A Cross-country Analysis - CHU, May Yen; LAW, Teik Hua; LAW, Siong Hook; LEE, Jin Chai (Journal of the Eastern Asia Society for Transportation Studies, 2024)
Existing empirical evidence points to an inverse U-shaped relationship between motorcycle ownership and per capita income. Motorists tended to select cheaper modes of transportation, such as motorcycles and mopeds under low purchasing power, which promote a greater motorcycle to private car ownership. Contrarily, urbanisation induced long distance travel and this possibly induces a rise in car ownership at a particular level of per capita income. This study assessed the effect of the consumer price index, as the proxy of purchasing power, urbanisation, road density and per capita income on motorcycle to private car ownership. The panel data analysis is applied over the period of 1963-2013 for 76 countries. The main finding of this study indicates that purchasing power, urbanisation and road density played important role on national private vehicle ownership in a country. Policy implications were discussed in the conclusion part of the study.